Becoming a Data Head : How to Think, Speak, and Understand Data Science, Statistics, and Machine Learning /: How to Think, Speak, and Understand Data Science, Statistics, and Machine Learning. (2021) - Gutman, Alex J; Goldmeier, Jordan
No abstract available